CURRENT APPROACH AND FACTORS LEADING TO ENDOMETRIAL HYPERPLASIA IN PREMENOPAUSE (World Bulletin of Public Health, 2022)
Endometrial hyperplastic processes (EH) is an extremely important, complex and versatile problem of practical gynecology. The tendency of GPE to a long, recurrent course, the absence of specific, pathognomonic symptoms, the complexity of differential diagnosis and the choice of treatment methods. In addition, this pathology is a proliferative process and, if left untreated for a long period of time, can be a background for the development of endometrial cancer. A steady increase in the incidence of cervical cancer, which ranks fourth among malignant tumors seen in women (after breast, lung, and colon cancer) and takes first place among tumors of the female genitalia, has been noted over the past 20 years.